Experience in caring for the older people with dementia in the home environment - Cruzeiro, Maria Gabriela Martins (2022)
Objective: to understand the experience of family caregivers in caring for older people with dementia in the home environment. Methods: a systematic search for qualitative studies and a thematic analysis was carried out to synthesize the results. Results: nine studies were included. Four analytical themes emerged. Recognizing dementia and unraveling care; "You are alone"; Limitations and lack of knowledge in caring for dementia; "It's a last resort [full institutionalization nursing home]." The older people’s loss of autonomy generated feelings of grief and loneliness. Limited knowledge about dementia has given rise to awkward care. Temporary care was perceived as a solution to the need for help. However, institutionalization was approached as a last alternative. Conclusion: the results obtained are important to provide support for the creation of more humanized public policies that consider comprehensive care, assist health professionals in providing care to older people with dementia and their families.